MicroSEQ® Salmonella spp. Detection Kit Using the Pathatrix® 10-Pooling Salmonella spp. Kit Linked Protocol Method Modification. (27th November 2019) - Wall, Jason; Conrad, Rick; Latham, Kathy; Liu, Eric
Abstract: Real-time PCR methods for detecting foodborne pathogens offer the advantages of simplicity and quick time to results compared to traditional culture methods. The addition of a recirculating pooled immunomagnetic separation method prior to real-time PCR analysis increases processing output while reducing bothcost and labor. This AOAC Research Institute method modification study validates the MicroSEQ ® Salmonella spp. Detection Kit [AOAC Performance Tested Method (PTM) 031001] linked with the Pathatrix ® 10-Pooling Salmonella spp. Kit (AOAC PTM 090203C) in diced tomatoes, chocolate, and deli ham. The Pathatrix 10-Pooling protocol represents a method modification of the enrichment portion of the MicroSEQ Salmonella spp. protocol. The results of the method modification were compared to standard cultural reference methods for diced tomatoes, chocolate, and deli ham. All threematrixes were analyzed in a paired study design. An additional set of chocolate test portions was analyzed using an alternative enrichment medium in an unpaired study design. For all matrixes tested, there were no statistically significant differences in the number of positive test portions detected by the modified candidate method compared to the appropriate reference method. The MicroSEQ Salmonella spp. protocol linked with the Pathatrix individual or 10-Pooling procedure demonstrated reliabilityas a rapid, simplified, method for the preparation of samples and subsequent detection of Salmonella in diced tomatoes, chocolate, and deliham.